2005
DOI: 10.1007/s00125-005-1867-3
|View full text |Cite
|
Sign up to set email alerts
|

Microarray profiling of isolated abdominal subcutaneous adipocytes from obese vs non-obese Pima Indians: increased expression of inflammation-related genes

Abstract: Aims/hypothesis: Obesity increases the risk of developing major diseases such as diabetes and cardiovascular disease. Adipose tissue, particularly adipocytes, may play a major role in the development of obesity and its comorbidities. The aim of this study was to characterise, in adipocytes from obese people, the most differentially expressed genes that might be relevant to the development of obesity. Methods: We carried out microarray gene profiling of isolated abdominal subcutaneous adipocytes from 20 non-obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
213
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(233 citation statements)
references
References 40 publications
15
213
1
2
Order By: Relevance
“…13 In addition, an upregulation of NOX4 in the adipose tissue of obese Pima Indians compared with lean subjects was detected. 44 Our study confirmed upregulation of adipose tissue NOX4 expression upon HFD feeding (Supplementary Figure S5). However, in view of the results of our current study NOX4 upregulation should be regarded as a defensive mechanism to limit adipose tissue expansion.…”
Section: Discussionsupporting
confidence: 80%
“…13 In addition, an upregulation of NOX4 in the adipose tissue of obese Pima Indians compared with lean subjects was detected. 44 Our study confirmed upregulation of adipose tissue NOX4 expression upon HFD feeding (Supplementary Figure S5). However, in view of the results of our current study NOX4 upregulation should be regarded as a defensive mechanism to limit adipose tissue expansion.…”
Section: Discussionsupporting
confidence: 80%
“…Subjects for adipose tissue biopsies were admitted as inpatients to our Clinical Research Center, and, after an overnight fast, underwent a subcutaneous abdominal needle biopsy under local anesthesia with 1% lidocaine. Collagenase digestion of the subcutaneous abdominal adipose tissue biopsy samples was performed as previously described (13,14). Briefly, the preadipocyte-containing infranatant was collected into a separate tube and washed several times with Hanks' balanced salt solution.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18] Weight reduction induces changes in the expression of various genes in AT. [19][20][21][22][23] A few studies have applied microarray technologies to study gene expression in AT of massively obese subjects either in comparison to lean subjects cross-sectionally 24,25 or after short-term weight reduction. 26,27 These studies have demonstrated downregulation in the expression of genes involved in inflammation and desaturation of fatty acids.…”
Section: Introductionmentioning
confidence: 99%